Handwriting status among Iranian primary school students: a cross-sectional study. (2nd February 2021) - Havaei, Naser; Mahmodzadeh, Mahdieh; Azad, Akram; Meimandi, Mahsa; Rezaei, Mandana; Kahjoogh, Mina Ahmadi; Mohammadi, Ahmad
Abstract : Background/Aims: Handwriting difficulties among school students are the primary reason for referral to school-based occupational therapy. Appropriate criteria and a complete view of the students' handwriting status are lacking in Iran. The purpose of this study was to gather comprehensive information about handwriting issues for therapists and related disciplines in Iran. Methods: In this cross-sectional study, the handwriting status of 1262 Persian-language elementary school students (grades 2 and 3) from governmental schools was surveyed using the Persian handwriting assessment tool. Results: There were statistically significant differences in handwriting components between second and third grade students except for word size and text slant. Handwriting components were different between boys and girls, and between right- and left-handed writers. Regression analysis revealed a positive relationships between age and grade and most of the handwriting components. Conclusions: The results of this study have implications for teachers, therapists and other specialists who work and research on handwriting status of typically healthy students and students who are disabled in Iran. Handwriting skills improve over time and it seems that girls and right-handed writers are better writers regarding legibility.